(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
The main objective is to investigate the irrationality of prescribing patterns of antibiotics in prescription. This helps in improvise rationality of antibiotics by enhancing quality of life and socio-economic status of patient. It is a prospective observational cohort study done at GBR Hospital, Narasaraopet, A.P. A total of 170 patients consisting of 101 males (59.4%) and 69 females (40.54%) were enrolled. Among these majority of patients 45 (26.47%) were in the age group of 41-50 years. 92 (54.12%) patients were prescribed with antibiotics in general medicine department. The most commonly prescribed antibiotics were Cephalosporin’s and tetracyclines. Majority of drugs 66.32% with single drug was prescribed in general medicine department followed by 23.68% in neurology. Of the 170 patients analyzed in various departments, it was observed that hospital physicians prescribed antibiotics more rationally with no banned drugs and lesser newer drugs. This study states that development of clinical pharmacy services is also necessary to improve rational prescribing of antibiotics. Utilizing of clinical pharmacy services shows benefit of patient health related outcomes and also improves the economic status of patients.